Process for the preparation of fepe-rare earth based catalysts with oxygen vacancies and use thereof
By introducing oxygen-vacant Gd2O3 and carbon nanotube composite supports into FePc catalysts, the problems of insufficient exposure of active sites and poor conductivity of FePc catalysts have been solved, achieving a high-activity, high-stability and low-cost oxygen reduction reaction, which promotes the development of fuel cells and metal-air batteries.
Patent Information
- Application Number
- CN202610881178.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-11-03
AI Technical Summary
Existing FePc catalysts suffer from problems such as insufficient exposure of active sites, poor conductivity, and easy desorption and deactivation in oxygen reduction reactions, making it difficult to achieve high activity, high selectivity, and long-term cycle stability. Furthermore, precious metal catalysts are expensive and have limited resources.
Using Gd2O3 with oxygen vacancies as a support, it is combined with activated carbon nanotubes and loaded with FePc to form a catalyst. By utilizing the electronic regulation of Gd2O3 and the high conductivity of carbon nanotubes, the interaction of active centers of the catalyst is enhanced, promoting O2 adsorption and activation.
This improved the activity and stability of the catalyst, reduced costs, enabled a highly efficient four-electron oxygen reduction reaction, and enhanced the performance of fuel cells and metal-air batteries.
Smart Images

Figure CN123033987A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalysis technology, specifically relating to a method for preparing FePc-rare earth-based catalysts with oxygen vacancies and their applications. Background Technology
[0002] Under the carbon neutrality strategy, developing efficient, clean, and sustainable energy conversion and storage technologies is of great significance for reducing dependence on fossil fuels, decreasing greenhouse gas emissions, and building a green and low-carbon energy system. Fuel cells and metal-air batteries, due to their advantages of high energy conversion efficiency, environmental friendliness, and high energy density, are considered important electrochemical energy devices supporting the utilization of new energy sources and the low-carbon energy transition. Among these, the oxygen reduction reaction (ORR) is a key cathode reaction in fuel cells and metal-air batteries. Its slow reaction kinetics directly affect the device's output power, energy conversion efficiency, and long-term operational stability. Based on different electron transfer pathways, ORRs are generally classified into four-electron reduction pathways and two-electron reduction pathways. Four-electron ORRs can directly reduce O2 to H2O or OH. - Four-electron ORR, with its higher electron transfer efficiency and energy utilization efficiency, is the most ideal oxygen reduction pathway in fuel cells and metal-air batteries. In contrast, two-electron ORR mainly generates H2O2, which easily leads to byproduct accumulation, active site deactivation, and decreased device efficiency. Therefore, developing oxygen reduction electrocatalysts that can promote the four-electron ORR pathway, suppress two-electron side reactions, and possess the advantages of high activity, high stability, and low cost is of great significance for improving the performance of fuel cells and metal-air batteries, promoting the development of clean energy technologies, and serving the goal of carbon neutrality. Currently, the most commonly used high-efficiency catalysts for ORR are platinum (Pt) and its alloys, etc., noble metal catalysts. Pt-based catalysts have high intrinsic ORR activity and superior four-electron oxygen reduction selectivity, and can effectively promote the conversion of O2 to H2O or OH-. -The direct conversion of oxygen to carbon dioxide (O2) has long been considered the performance benchmark for ORR catalysts in fuel cells and metal-air batteries. However, precious metals such as Pt are limited in reserves and expensive, and are easily affected by factors such as methanol cross-contamination, CO poisoning, particle agglomeration, and dissolution migration during actual operation, leading to a decrease in catalytic activity and stability, thus limiting their large-scale commercial application. Therefore, developing low-cost, high-activity, high-selectivity, and high-stability non-precious metal ORR catalysts is an important direction for promoting the development of clean energy devices such as fuel cells and metal-air batteries. Among many non-precious metal ORR catalysts, iron phthalocyanine (FePc) exhibits certain catalytic activity in the oxygen reduction reaction due to its Fe-N4 active center, which has a structure similar to metal porphyrins, and can simulate the adsorption and activation process of oxygen molecules by precious metal catalysts. At the same time, FePc has advantages such as well-defined structure, low cost, and strong molecular designability, and is considered a class of non-precious metal molecular catalysts with application potential. However, using FePc alone still has significant shortcomings: its molecules are prone to π-π stacking, leading to insufficient exposure of active sites; its poor conductivity hinders rapid electron transport during the reaction process; and it is susceptible to problems such as molecular desorption, structural damage, or deactivation of active centers during electrocatalytic reactions, resulting in insufficient catalytic stability. Furthermore, the adsorption strength of FePc for O2 and key ORR intermediates still needs further regulation; otherwise, it will be difficult to simultaneously achieve high activity, high four-electron selectivity, and long-term cycling stability. Summary of the Invention
[0003] This invention addresses the shortcomings of existing technologies by providing abundant defect sites through a metal oxide support with oxygen vacancies, thereby regulating the interfacial electronic structure, enhancing O2 adsorption and activation capabilities, and improving the interaction between the FePc active center and the support. Based on this, this invention uses Gd₂O₃ with oxygen vacancies as the functional regulating component and loads FePc onto the surface of an activated carbon nanotube / oxygen-vacancy Gd₂O₃ composite support. Utilizing the high conductivity of carbon nanotubes, the electronic regulation effect of oxygen-vacancy Gd₂O₃, and the ORR catalytic ability of the Fe-N₄ active center in FePc, a low-cost, highly active, and highly stable non-precious metal oxygen reduction catalyst is constructed and applied to the four-electron oxygen reduction reaction in electrochemical energy conversion devices such as fuel cells and metal-air batteries.
[0004] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a FePc-rare earth-based catalyst with oxygen vacancies includes the following steps:
[0006] S1: Carbon nanotubes are activated by calcination under an inert atmosphere to obtain activated carbon nanotubes;
[0007] S2: The activated carbon nanotubes and gadolinium nitrate hexahydrate are stirred and mixed in a solvent, and the resulting mixture is calcined under a mixed atmosphere of argon and hydrogen to obtain a carbon nanotube / oxygen vacancy Gd2O3 composite support.
[0008] S3: The carbon nanotube / oxygen vacancy Gd2O3 composite support and FePc are stirred and mixed in an organic solvent, so that FePc is adsorbed on the composite support.
[0009] S4: Wash the product obtained in step S3, separate the solid part, and dry it to obtain the FePc-Gd2O3-based catalyst with oxygen vacancies.
[0010] Preferably, the calcination activation temperature in step S1 is 450–550°C.
[0011] Preferably, the calcination temperature in step S2 is 700–900°C; the calcination time is 2–4 hours; and the mass ratio of the carbon nanotube / oxygen vacancy Gd2O3 composite support to FePc in step S3 is 1:1–3.
[0012] Preferably, in step S2, the mass ratio of carbon nanotubes to gadolinium nitrate hexahydrate is 1:5 to 1:20.
[0013] Preferably, the organic solvent in step S3 is N,N-dimethylformamide, and the stirring time is 6 to 24 hours.
[0014] Preferably, the detergent in step S4 is ultrapure water and / or ethanol, and the drying is vacuum drying for 6 to 24 hours.
[0015] Preferably, the mixing ratio of hydrogen to argon in step S2 is 5%:95%.
[0016] Preferably, the inert gas in step S1 is selected from at least one of argon, nitrogen, and helium.
[0017] This invention also protects the catalysts prepared by the FePc-Gd2O3-based catalyst preparation method.
[0018] The FePc-Gd₂O₃-based catalyst with oxygen vacancies prepared in this invention uses activated carbon nanotubes as a conductive support. A composite catalytic system is constructed by loading Gd₂O₃ with oxygen vacancies onto its surface and further adsorbing iron phthalocyanine (FePc). This catalyst, when used as a non-noble metal oxygen reduction reaction (ORR) electrocatalyst, has the following advantages:
[0019] 1) Synergistic Advantages of Interface Structure. This invention combines FePc, Gd₂O₃ with oxygen vacancies, and activated carbon nanotubes to form a multi-component synergistic catalytic structure. Specifically, the Fe-N₄ structure in FePc serves as an active center for the ORR reaction, promoting O₂ adsorption and activation; Gd₂O₃ with oxygen vacancies provides abundant defect sites, modulating the electronic structure of the catalyst surface and optimizing the adsorption strength of key ORR intermediates; and activated carbon nanotubes improve the overall conductivity of the catalyst, promoting electron transport. The synergistic effect of these three components enhances the catalytic activity and selectivity of the oxygen reduction reaction.
[0020] 2) Effectively reduces catalyst costs. The catalyst described in this invention does not contain precious metal elements such as Pt, and is mainly composed of FePc, Gd2O3, and carbon nanotubes. The raw materials are relatively widely available and have low costs. Compared with traditional Pt-based precious metal ORR catalysts, this catalyst can significantly reduce preparation costs, providing a new approach for the application of non-precious metal oxygen reduction catalysts in electrochemical energy devices such as fuel cells and metal-air batteries.
[0021] 3) Improved catalytic stability of FePc. When FePc is used alone, it is prone to problems such as molecular aggregation, poor conductivity, insufficient exposure of active sites, and easy desorption or deactivation during the reaction. This invention, by loading FePc onto the surface of an activated carbon nanotube / oxygen vacancy Gd₂O₃ composite support, can effectively enhance the interaction between FePc and the support, improve the dispersion of FePc, increase the utilization rate of active sites, and to a certain extent improve the structural stability and cycle life of the catalyst.
[0022] 4) The preparation method is simple and easy to promote. The present invention uses carbon nanotube activation, oxygen vacancy Gd2O3 loading, FePc physical adsorption, filtration, vacuum drying and grinding to prepare the target catalyst. The overall process is simple, the reaction conditions are mild, and no complex equipment or precious metal precursors are required. It has good operability and potential for promotion and application. Attached Figure Description
[0023] Figure 1 This is a scanning electron microscope image of the FePc-Gd2O3-based catalyst with oxygen vacancies prepared in Example 1 of the present invention.
[0024] Figure 2 This is a TEM image of the FePc-Gd2O3-based catalyst with oxygen vacancies prepared in Example 1 of the present invention.
[0025] Figure 3 The image shows the XRD pattern of the FePc-Gd2O3-based catalyst with oxygen vacancies prepared in Example 1 of this invention.
[0026] Figure 4The electrochemical performance test diagrams of the FePc-Gd2O3 group with oxygen vacancies prepared in Example 1 of the present invention are shown (a, b, c and d represent LSV curve, Tafel slope, stability data and electrochemical active area, respectively). Detailed Implementation
[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods used in the embodiments of the present invention are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available reagents and materials.
[0028] Example 1: A method for preparing a FePc-Gd2O3-based catalyst with oxygen vacancies, comprising the following steps:
[0029] Step 1, Activate carbon nanotubes:
[0030] Take 0.1g of carbon nanotubes and place them in a ceramic boat. Put the boat into a tube furnace and calcine it at 500 degrees Celsius under an argon atmosphere to activate the carbon nanotubes.
[0031] The second step involves thoroughly mixing carbon nanotubes and gadolinium nitrate hexahydrate (ratio 1:10) in ethanol, placing the mixture in a ceramic boat, and then placing it in a tube furnace. The mixture is then calcined at 800 degrees Celsius for 3 hours under a mixed atmosphere of argon and hydrogen to prepare a carbon nanotube / oxygen vacancy Gd2O3 composite carrier.
[0032] The third step involves placing the composite carrier and FePc in N,N-dimethylformamide (DMF) at a ratio of 1:2 and stirring for 12 hours to allow for the physical adsorption of FePc.
[0033] The fourth step involves washing the product obtained in the third step several times with ultrapure water and ethanol, separating the product from the relevant compounds, and then vacuum drying the solid portion for 12 hours to obtain the target catalyst.
[0034] Example 2: A method for preparing a FePc-Nd2O3-based catalyst with oxygen vacancies, comprising the following steps:
[0035] Step 1, Activate carbon nanotubes:
[0036] Take 0.1g of carbon nanotubes and place them in a ceramic boat. Then place the boat in a tube furnace and calcine it at 500 degrees Celsius under an argon atmosphere to activate the carbon nanotubes.
[0037] The second step involves thoroughly mixing carbon nanotubes and neodymium nitrate hexahydrate (ratio 1:10) in ethanol, placing the mixture in a ceramic boat, and then calcining it in a tube furnace at 800 degrees Celsius for 3 hours under a mixed atmosphere of argon and hydrogen to prepare a carbon nanotube / oxygen vacancy Nd2O3 composite carrier.
[0038] The third step involves placing the composite carrier and FePc in N,N-dimethylformamide (DMF) at a ratio of 1:2 and stirring for 12 hours to allow for the physical adsorption of FePc.
[0039] Fourth, the product obtained in step three was washed several times with ultrapure water and ethanol to separate the product from the relevant compounds. The solid fraction was then vacuum dried for 12 hours to obtain the target catalyst.
[0040] Example 3: A method for preparing a FePc-Er2O3-based catalyst with oxygen vacancies, comprising the following steps:
[0041] Step 1, Activate carbon nanotubes:
[0042] Take 0.1g of carbon nanotubes and place them in a ceramic boat. Then place the boat in a tube furnace and calcine it at 500 degrees Celsius under an argon atmosphere to activate the carbon nanotubes.
[0043] The second step involves thoroughly mixing carbon nanotubes and erbium nitrate hexahydrate (ratio 1:10) in ethanol, placing the mixture in a ceramic boat, and then calcining it in a tube furnace at 800 degrees Celsius for 3 hours under a mixed atmosphere of argon and hydrogen to prepare a carbon nanotube / oxygen vacancy Er2O3 composite support.
[0044] The third step involves placing the composite carrier and FePc in N,N-dimethylformamide (DMF) at a ratio of 1:2 and stirring for 12 hours to allow for the physical adsorption of FePc.
[0045] Fourth, the product obtained in step three was washed several times with ultrapure water and ethanol to separate the product from the relevant compounds. The solid fraction was then vacuum dried for 12 hours to obtain the target catalyst.
[0046] Example 4: A method for preparing a FePc-Tb2O3-based catalyst with oxygen vacancies, comprising the following steps:
[0047] Step 1, Activate carbon nanotubes:
[0048] Take 0.1g of carbon nanotubes and place them in a ceramic boat. Then place the boat in a tube furnace and calcine it at 500 degrees Celsius under an argon atmosphere to activate the carbon nanotubes.
[0049] The second step involves thoroughly mixing carbon nanotubes and terbium nitrate hexahydrate (ratio 1:10) in ethanol, placing the mixture in a ceramic boat, and then calcining it in a tube furnace at 800 degrees Celsius for 3 hours under a mixed atmosphere of argon and hydrogen to prepare a carbon nanotube / oxygen vacancy Tb2O3 composite carrier.
[0050] The third step involves placing the composite support and FePc in N,N-dimethylformamide (DMF) and stirring for 12 hours to allow for the physical adsorption of FePc.
[0051] Fourth, the product obtained in step three was washed several times with ultrapure water and ethanol to separate the product from the relevant compounds. The solid fraction was then vacuum dried for 12 hours to obtain the target catalyst.
[0052] Figure 1 This is a scanning electron microscope (SEM) image of the catalyst prepared in Example 1 of the present invention. The SEM image reveals that a large number of nanoparticles are loaded onto the carbon nanotubes.
[0053] Figure 2 This is a transmission electron microscope (TEM) image of the catalyst prepared in Example 1 of the present invention. The TEM image clearly shows that a large number of nanoparticles are loaded on the carbon nanotubes.
[0054] Figure 3 The image shows a comparison of the XRD patterns of the catalyst prepared in Example 1 of this invention. It can be seen that the XRD peaks of the prepared catalyst correspond to the characteristic diffraction peaks of Gd2O3 (PDF#43-1014) and FePc (PDF#22-1771), indicating that the material synthesized by the method of this application is a novel material containing rare earth oxides Gd2O3 and FePc.
[0055] Figure 4 This is a comparison chart of the electrochemical performance of Example 1. In this invention, a 0.1M KOH electrolyte with pH=13 was used, and the ORR performance of the catalyst obtained in Example 1, commercial 20%wt (platinum content higher than that of this application) Pt / C, and unmodified FePc were tested in this electrolyte. Figure 4 a represents the LSV curve in the ORR performance test, for comparison (the test used 0.4 mg / cm³). 2 The catalyst prepared in Example 1 showed significant improvements in both half-wave potential and onset potential, with the half-wave potential reaching 0.88 V, which is in the upper-middle range among all ORR catalysts. Figure 4b represents the Tafel slope in the ORR performance test. As can be seen from the figure, the modified FePc-Gd2O3-based catalyst has the lowest Tafel slope, which exceeds that of the Pt / C and the unmodified FePc-based catalyst. This proves that the FePc-Gd2O3-based catalyst has a larger output current at the same voltage, and thus higher open-circuit voltage and discharge power when used in fuel cells and zinc-air batteries. Figure 4 As can be seen from c, the stability of the modified FePc-Gd2O3-based catalyst is significantly improved compared to the unmodified FePc-based catalyst. Figure 4 As can be seen from d, the modified FePc-Gd2O3-based catalyst has the largest electrochemical active area.
[0056] Obviously, the specific implementation schemes described above are merely a further detailed explanation of the purpose, technical solution and beneficial effects of the present invention. It should be understood that the above descriptions are only specific examples of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing FePc-rare earth-based catalysts with oxygen vacancies, characterized in that, Includes the following steps: S1: Carbon nanotubes are activated by calcination under an inert atmosphere to obtain activated carbon nanotubes; S2: The activated carbon nanotubes and gadolinium nitrate hexahydrate are stirred and mixed in a solvent, and the resulting mixture is calcined under a mixed atmosphere of argon and hydrogen to obtain a carbon nanotube / oxygen vacancy Gd2O3 composite support. S3: The carbon nanotube / oxygen vacancy Gd2O3 composite support and FePc are stirred and mixed in an organic solvent, so that FePc is adsorbed on the composite support. S4: Wash the product obtained in step S3, separate the solid part, and dry it to obtain the FePc-Gd2O3-based catalyst with oxygen vacancies.
2. The method for preparing the FePc-rare earth-based catalyst with oxygen vacancies according to claim 1, characterized in that, The calcination and activation temperature in step S1 is 450–550 °C.
3. The preparation method according to claim 1, characterized in that, In step S2, the calcination temperature is 700–900℃ and the calcination time is 2–4 hours. In step S3, the mass ratio of carbon nanotube / oxygen vacancy Gd2O3 composite support to FePc is 1:1–3.
4. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of carbon nanotubes to gadolinium nitrate hexahydrate is 1:5 to 1:
20.
5. The preparation method according to claim 1, characterized in that, In step S3, the organic solvent is N,N-dimethylformamide, and the stirring time is 6 to 24 hours.
6. The preparation method according to claim 1, characterized in that, In step S4, the detergent is ultrapure water and / or ethanol, and the drying is vacuum drying for 6 to 24 hours.
7. The preparation method according to claim 1, characterized in that, In step S2, the mixing ratio of hydrogen to argon is 5%:95%.
8. The preparation method according to claim 1, characterized in that, In step S1, the inert gas is selected from at least one of argon, nitrogen, and helium.
9. A catalyst prepared by the method for preparing the oxygen vacancy FePc-rare earth-based catalyst of claim 1.
10. The application of the catalyst of claim 9 in the oxygen reduction reaction.
